How can servant leadership arouse to innovative work behavior? - Shofia Amin; Zulfina Adriani; Fitri Widiastuti (INOVASI, 2022)
This study examined the role of servant leadership in encouraging innovative work behavior of civil servants through increased employee engagement. This study used a quantitative method   by distributing   a   list   of   questions   to 116 Aparatur Sipil Negara (ASN) from several institutions in Jambi City. The primary data were analyzed using SEM-SmartPLS. The results showed that servant leadership had no significant positive effect on innovative work behavior, but servant leadership positively affected employee engagement. Moreover, employee engagement also has a significant positive impact on innovative work behavior. Thus, employee engagement is a complete mediation in the relationship between servant leadership and innovative work behavior. The results indicated that innovative behavior could be increased by enhancing employee engagement stimulated by servant leadership.